The current state of the quality of homeopathic clinical research - Patricia M. Herman; Cindy C. Crawford; Margaret A. Maglione; Sydne J. Newberry; Paul S. Amieux; Kimberlee Blyden-Taylor; Raheleh Khorsan; Marcia Prenguber; Elizabeth Rice; Andy Shollar; Tiesha Tyson; Nazanin Vassighi; et al. (Complementary Therapies in Medicine, 2025)
Homeopathy is a system of therapeutics that treats disease with highly diluted substances based on the Law of Similars, which holds that “like cures like.” Despite widespread use, homeopathy lacks a comprehensive and robust evidence base.We examined the state of homeopathic clinical research by critically assessing the overall quality of peer-reviewed, recently published, English-language, homeopathic clinical research in terms of internal, external, and model validity using standard and homeopathic-specific instruments. Further, we convened an international panel of nine experts in research methods and homeopathy to identify gaps in homeopathic research and prioritize areas for future study.We reviewed 99 clinical research studies targeting a wide range of populations and conditions. Studies were conducted in Western and Asian countries, with the largest number (30 percent) conducted in India. Of the 99 studies reviewed, 85 were controlled trials; 79 of these were randomized. There were many areas where the quality of the studies could be improved. About two-thirds of the 85 controlled trials had either high (42 percent) or unclear (24 percent) risk of bias according to internationally recognized standards for internal validity. Of the 14 observational (cohort) studies, over one-third did not control for important confounders in the outcome analyses. Regarding external validity, adherence was reported in less than a third of studies (n=31). Forty percent of studies (79 % of observational studies) did not report on safety. Regarding model validity, fewer than two-thirds of the studies were consistent with homeopathic principles.Our expert panel was mixed on whether the homeopathic research literature was missing important populations and/or conditions, and they suggested a variety of priority areas. Panelists also expressed a variety of opinions about the types of homeopathy that should be prioritized for future study but also noted that since homeopathic practice differs by country, each country may have different priorities.Panelists agreed with the findings of the literature review that the research literature was at least somewhat deficient in all three types of validity. Although our assessment of validity was [by necessity] based only on what was reported, this assessment suggests the need for both better reporting and higher quality research. They recommended the use of reporting guidelines to improve all types of validity, the identification of exemplar studies to help guide researchers to improve internal validity, and, given the limitations of the instruments available to measure external and model validity, that these instruments be validated and configured to provide summary scores. Finally, substantial discussion addressed the need to bring more research expertise into homeopathic studies, both by better training homeopathic researchers and by collaborating with experienced conventional medicine research groups.